Analysing the slogan "LUBER" in Indonesia's 2024 general election: A critical discourse analysis - Wajdi, Majid; Asrumi, Asrumi (Journal of Language and Pragmatics Studies, 2024)
The year 2024 marks a crucial moment for Indonesia as the nation prepares for its five-yearly general election to elect a new president. At the forefront of this electoral process is the distinctive slogan “LUBER,” representing the principles of Langsung (Direct), Umum (Public), Bebas (Free), and Rahasia (Secret). This study seeks to explore into the form, function, and meaning of the “LUBER” slogan, aiming to unravel its significance in the socio-political landscape of Indonesia. The primary purpose of this research is to dissect the “LUBER” slogan, examining its linguistic and rhetorical features, its intended functions within the electoral context, and the underlying meanings it conveys to the Indonesian electorate. By undertaking this analysis, we aim to provide a comprehensive understanding of how the slogan operates as a discourse tool in shaping public perception and participation in the upcoming general election. The study employs a two-fold methodological approach, incorporating document study and critical discourse analysis (CDA). Document study involves a comprehensive review of official election materials, speeches, and campaign documents, while CDA focuses on dissecting the language, rhetoric, and discursive strategies employed in the “LUBER” slogan. The analysis reveals that the “LUBER” slogan strategically combines linguistic elements to convey a message of transparency, inclusivity, freedom, and confidentiality in the electoral process. Through CDA, we uncover how the slogan operates as a powerful discourse tool, influencing public opinion and fostering a sense of civic responsibility. Additionally, the study identifies subtle nuances in the language used, shedding light on the socio-political implications of the “LUBER” slogan.In conclusion, the “LUBER” slogan serves as a multifaceted discourse tool in Indonesia’s 2024 general election, embodying the principles of transparency and democratic values. The linguistic and rhetorical features of the slogan play a pivotal role in shaping public perception and encouraging active civic participation. This study contributes to a deeper understanding of the role of political discourse in shaping electoral processes and underscores the importance of linguistic analysis in decoding the complexities of political communication.